Titanic - Marriott, Leo 1944- (PRC, 1997)
Recounts the first and only voyage of the Titanic
Keywords: Titanic (Steamship); Shipwrecks / North Atlantic Ocean; Titanic (Ship); Naufrages / Atlantique Nord; Shipwrecks; North Atlantic Ocean